Improvement of gelation properties of soy protein isolate emulsion induced by calcium cooperated with magnesium. (March 2019) - Wang, Xufeng; Luo, Kaiyun; Liu, Shutao; Adhikari, Benu; Chen, Jie
Abstract: The aim oft his study is to investigate the cooperation effects of calcium (CaSO4 ) and magnesium (MgCl2 and MgSO4 ) salts on the rheological and microstructural properties, and water holding capacity (WHC) of soy protein isolate (SPI) emulsion-based tofu gels. Small-deformation rheology indicated that the aggregation power of the three coagulants follows the order of MgCl2  > MgSO4  > CaSO4, and the coagulants containing MgSO4 (5 and 10 mM) and MgCl2 (5 mM) promote to produce stronger gels with greater gel firmness and rigidity. When compared with single CaSO4 as the coagulant, a low concentration of Mg 2+ helped to form compact protein aggregates and facilitated gel homogeneity and resistance to deformation. The WHC of the gels was significantly enhanced (p < 0.05) by the action of 5 mM MgSO4 . The relationships between aggregates induced by the coagulants and gel properties, as well as the influencing mechanism were discussed. The findings provide valuable information for understanding the coagulant-related gelation mechanism of protein and the application of SPI emulsion-based gels with improved properties in food industry. Highlights: Cooperation effects of calcium and magnesium salts on the gelation of SPI emulsion were investigated. Low concentration of Mg 2+ facilitated gel homogeneity and resistance to deformation. High concentration of Mg 2+ increased the coarseness of SPI emulsion gels. Water-holding capacity of the gels was significantly enhanced by the action of 5 mM MgSO4 .